PENGEMBANGAN SISTEM INFORMASI MANAJEMEN INVENTORI SEKOLAH DENGAN PEMODELAN UNIFIED MODELLING LANGUAGE PADA YAYASAN PERGURUAN GAJAH MADA - Grace Apulisa Ginting; Sariadin Siallagan; Wanra Tarigan; Anjar Pinem (Jurnal Riset Multidisiplin Edukasi, 2025)
The Inventory management at SD yayasan Perguruan Gajah Mada has been carried out manually using paper-based records, which often leads to several issues such as delays in data retrieval, risk of data loss, and inaccuracies in Inventory reports. These conditions affect the effectiveness of managing the school’s facilities and infrastructure. This study aims to develop a School Inventory Management Information System that facilitates recording, managing, and reporting inventory more effectively, efficiently, and accurately by applying Unified Modelling Language (UML) in the system design process. The research adopts a research and development (R&D) approach, consisting of system requirements analysis, system design using UML (use case diagram, activity diagram, class diagram, and sequence diagram), system implementation, and testing using the black-box method to ensure proper system functionality. The inventory management information system developed using UML at SD Yayasan Perguruan Gajah Mada proves to improve efficiency, effectiveness, and accuracy in managing school inventory. This system is expected to provide a sustainable solution in supporting the management of educational facilities and infrastructure.